KAJIAN SIFAT SENSORIS TORTILA YANG DISUBSTITUSI TEPUNG BIJI NANGKA - Wandi Dolongseda; Maya M. Ludong; Gregoria S.S. Djarkasi (Universitas Sam Ratulangi, 2017)
ABSTRACTThis study aims to evaluate the level of acceptance of tortillas products made from raw corn starch nikstamal with substitution of jackfruit seed flour, Based on sensory properties with broken power parameters, taste,color,Aroma and texture.This research use Completely Randomized Design (RAL) with 4 treatment that is A (without addition of jackfruit seed flour),B (25% jackfruit flour), C (50% jackfruit flour), D (75% jackfruit flour).Each treatment was repeated 3 times. The results showed that tortila treatment B (25% jackfruit flour: 75% maize) was not significantly different with treatment A (0% jackfruit flour: 100% maize).But significantly different from the C treatment (50% jackfruit seed flour) and D (75% jackfruit flour).Keywords: Tortilla, Jackfruit Seeds, Nikstamal Corn Flour.